Determining the Scientific and Historical Value of Manuscripts: The Basics and the Practical Requirements - Alsharaifi, Hasan; Idriz, Mesut; Okleh, Issam (Al-Adab Journal, 2024)
Islamic manuscripts are one of the quintessential icons of Islamic civilization. Manuscripts are objects of knowledge as much as they are objects of cultural heritage. Hence, granting access to their content should be one of the main priorities for Arab heritage institutions. Yet, when compared to western heritage institutions, Arab heritage institutions lag behind when it comes to providing access to manuscripts in their custody. This paper is of the opinion there is a problem with the way Arab heritage institutions perform their work. More specifically, Arab heritage institutions lack direction. Solution as this paper proposes is through the right orientation manifested in processing manuscripts according to their historical and scientific value. Hence, this paper will explore the basics of determining the historical and scientific value of manuscripts as well as put forth a discussion about the practical requirements to determine that value.